2010
DOI: 10.2967/jnumed.110.076794
|View full text |Cite
|
Sign up to set email alerts
|

Different Modes of Transport for 3H-Thymidine, 3H-FLT, and 3H-FMAU in Proliferating and Nonproliferating Human Tumor Cells

Abstract: The basis for the use of nucleoside tracers in PET is that activity of the cell-growth–dependent enzyme thymidine kinase 1 is the rate-limiting factor driving tracer retention in tumors. Recent publications suggest that nucleoside transporters might influence uptake and thereby affect the tracer signal in vivo. Understanding transport mechanisms for different nucleoside PET tracers is important for evaluating clinical results. This study examined the relative role of different nucleoside transport mechanisms i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
42
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 25 publications
7
42
1
Order By: Relevance
“…In previous in vitro work by our group, we reported that plateau-phase cultures of A549 cells have lower levels of ENT1 than proliferating cultures of A549 cells [2]. Our observation and those of Cass et al [10] and Coe et al [11] suggest that ENT1 levels are proliferation dependent.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…In previous in vitro work by our group, we reported that plateau-phase cultures of A549 cells have lower levels of ENT1 than proliferating cultures of A549 cells [2]. Our observation and those of Cass et al [10] and Coe et al [11] suggest that ENT1 levels are proliferation dependent.…”
Section: Introductionsupporting
confidence: 76%
“…The use of FLT uptake and retention as a surrogate marker for tumor proliferation is based on the assumption that thymidine kinase-1 (TK1, a cytosolic enzyme) activity up-regulated in S phase is the primary factor driving FLT uptake and retention in tumors [1]. While TK1 is an absolute requirement for radiotracer accumulation [2], variations in levels of the equilibrative nucleoside transporter-1 (ENT1), which facilitate FLT transport into cells, have been shown to modify intracellular peak levels of FLT [2, 3]. …”
Section: Introductionmentioning
confidence: 99%
“…1 G and H), further supporting the utility of this probe for imaging dCK activity. (27,28). As shown in Fig.…”
mentioning
confidence: 80%
“…Among the nucleosides, thymidine is exclusively used in the DNA structure. After entering the cells by multiple different transporters passively or actively (3,4), thymidine is phosphorylated into a more polarized molecule and cannot freely exit the cells. This mechanism has been used to accurately measure DNA synthesis in cell cultures using 3 H-thymidine.…”
Section: Proliferation Imaging and Its Role In Practicementioning
confidence: 99%